Histopathological Profile of Cholecystectomy Specimens at a Tertiary Care Center: A Retrospective Study - Udita Bajaj; Dimple Kalsi; Preeti Bajaj; Sheela Chikhalikar (Journal of the Scientific Society)
Introduction: Gallbladder is one of the most frequently received specimens in any histopathology laboratory. Its diseases may present with a varied spectrum ranging from congenital anomalies, cholelithiasis, and inflammatory or noninflammatory lesions to noninvasive and invasive neoplasms. Cholelithiasis (gallstones) is the most common lesion and accounts for more than 95% of gallbladder diseases and affects 10%–20% of the adult population. The incidence is 2–4 times higher in females than in males. Aims and Objectives: This study was designed to study the histopathological spectrum of gall bladder diseases in the population, study the most common gall bladder diseases in cholecystectomy specimens, and study the frequency of gall bladder carcinoma. Methodology: This retrospective observational study was done in the Pathology department at a tertiary care hospital and research center, from September 2016 to September 2023. Tissue was fixed in 10% buffered formalin and then processed by the routine paraffin embedding techniques. Sections were cut at 4–5 μ thickness and stained with hematoxylin and eosin stains. Special stains were done if required for confirmation. All the slides were analyzed and reported by a trained histopathologist. Results: Females were affected more as compared to males. The commonest age group affected was 41-50 years. Gallstones were observed in 33.58% of patients. Gallbladder neoplasm was rare and incidental findings. Conclusion: Gallbladder disease demonstrated a diverse spectrum of histopathological changes in the cholecystectomy specimens and showed female preponderance. Gallbladder carcinoma was observed as a rare occurrence and was an incidental finding mainly. Hence, a microscopic (histopathological) examination is required for every cholecystectomy specimen.